Dissimilarity of vertebrate trophic interactions reveals spatial uniqueness but functional redundancy across Europe - Gaüzère, Pierre; Botella, Christophe; Poggiato, Giovanni; O'Connor, Louise, M.J.; Di Marco, Moreno; Dragonetti, Chiara; Maiorano, Luigi; Renaud, Julien; Thuiller, Wilfried (Current Biology, 2023)
International audience Identifying areas that contain species assemblages not found elsewhere in a region is central to conservation planning. Species assemblages contain networks of species interactions that underpin species dynamics, ecosystem processes, and contributions to people. Yet the uniqueness of interaction networks in a regional context has rarely been assessed. Here, we estimated the spatial uniqueness of 10,000 terrestrial vertebrate trophic networks across Europe (1,164 species, 50,408 potential interactions) based on the amount of similarity between all local networks mapped at a 10 km resolution. Our results revealed more unique networks in the Arctic bioregion, but also in southern Europe and isolated islands. We then contrasted the uniqueness of trophic networks with their vulnerability to human footprint and future climate change and measured their coverage within protected areas. This analysis revealed that unique networks situated in southern Europe were particularly exposed to human footprint and that unique networks in the Arctic might be at risk from future climate change. However, considering interaction networks at the level of trophic groups, rather than species, revealed that the general structure of trophic networks was redundant across the continent, in contrast to species’ interactions. We argue that proactive European conservation strategies might gain relevance by turning their eyes toward interaction networks that are both unique and vulnerable.